2003
DOI: 10.1002/hlca.200390247
|View full text |Cite
|
Sign up to set email alerts
|

New Acylated Saponins from Polygala myrtifolia

Abstract: The ten new acylated presenegenin ( (2b,3b,4a)-2,3,27-trihydroxyolean-12-ene-23,28-dioic acid) glycosides 1 ± 10 have been isolated by successive MPLC from the roots of Polygala myrtifolia L. as five inseparable mixtures of the trans-and cis-4-methoxycinnamoyl derivatives, i.e., myrtifoliosides A 1 /A 2 (1/2), B 1 /B 2 (3/4), C 1 /C 2 (5/6), D 1 /D 2 (7/8), and E 1 /E 2 (9/10). Their structures were elucidated mainly by extensive spectroscopic experiments, including 2D NMR techniques, as 3- (7) and its cis-iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…This indicated that 1/2 was a mixture of (E)-and (Z)-4-methoxycinnamoyl triterpene glycosides. Such an (E)/(Z)-isomer behavior of the 4-methoxycinnamoyl moiety in MeOH solutions under light has often been described in many saponins from the Polygalaceae like P. arenaria [5] or P. myrtifolia [6]. (2)) revealed the (1 !…”
mentioning
confidence: 83%
See 2 more Smart Citations
“…This indicated that 1/2 was a mixture of (E)-and (Z)-4-methoxycinnamoyl triterpene glycosides. Such an (E)/(Z)-isomer behavior of the 4-methoxycinnamoyl moiety in MeOH solutions under light has often been described in many saponins from the Polygalaceae like P. arenaria [5] or P. myrtifolia [6]. (2)) revealed the (1 !…”
mentioning
confidence: 83%
“…After extensive 2D-NMR spectroscopic analysis and subtraction of the signals of the glucopyranosyl moiety of the prosapogenin, the signals of six sugar units linked to C(28) of the presenegenin remained, which were identified as Fuc, Rha, Xyl, Gal, Ara, and apiofuranosyl (Api). This latter was determined to be in the b-anomeric form by comparing its spectroscopic data with literature values [6]. Furthermore it was assumed to have the D-configuration normally found in nature.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…8,9 Correlations observed in the HMBC spectrum between signals at υ H 4.85 (1H, d, J D 7.6 Hz, GlcA-1) and υ C 90.2 (C-3), and in the NOESY spectrum between υ H 4.85 (GlcA-1) and υ …”
Section: Resultsmentioning
confidence: 99%
“…3)-a-L-arabinopyranosyl-and is substituted by the same acyl residues as in 32/33 and 34/35, respectively. The five pairs of presenegenin glycosides from P. myrtifolia (40/41-48/49) (Haddad et al, 2003) are substituted at the position 4 of the fucopyranosyl unit by a E/Z-4-methoxycinnamoyl group whereas the glycosides of Carpolobia alba (50-52) are substituted at the positions 3 and 4 by one acetyl group (Mitaine-Offer et al, 2002). Compounds 50 and 51 are common to both species C. alba and C. lutea.…”
Section: Introductionmentioning
confidence: 99%